Individual Differences in Children’s Preference to Learn From a Confident Informant - Juteau, Aimie-Lee; Cossette, Isabelle; Millette, Marie-Pier; Brosseau-Liard, Patricia (Frontiers in Psychology, 2019)
Past research has demonstrated that children can use an informant’s confidence level to selectively choose from whom to learn. Yet, in any given study, not all children show a preference to learn from the most confident informant. Are individual differences in this preference stable over time and across learning situations? In two studies, we evaluated the stability of preschoolers’ performance on selective learning tasks using confidence as a cue. The first study (N = 48) presented children with the same two informants, one confident and one hesitant, and the same four test trials twice with a 1-week delay between administrations. The second study (N = 50) presented two parallel tasks with different pairs of informants and test trials one after the other in the same testing session. Correlations between administrations were moderate in the first study and small in the second study, suggesting that children show some stability in their preference to learn from a confident individual but that their performance is also influenced by important situational factors, measurement error or both. Implications for the study of individual differences in selective social learning are discussed.